2015
DOI: 10.1016/j.ajpath.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expansion of Gastric Mucosal Doublecortin-Like Kinase 1–Expressing Cells in Response to Parietal Cell Loss Is Regulated by Gastrin

Abstract: Doublecortin-like kinase 1 (Dclk1) is considered a reliable marker for tuft cells in the gastrointestinal tract. We investigated the dynamic changes of tuft cells associated with mouse models of oxyntic atrophy and metaplasia in the stomach. Increases in the numbers of Dclk1-positive tuft cells were observed in several models of parietal cell loss. However, the expanded population of Dclk1-expressing cells showed a morphologically distinct structure in apical microvilli and acetylated microtubules, which was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…Results reported as a part of a previous larger study 32 indicate that Lrig1-expressing cells are able to contribute to formation of Tuft cells, suggesting their role in tissue maintenance. While this manuscript was under consideration, another study by Choi et al .…”
Section: Discussionmentioning
confidence: 72%
“…Results reported as a part of a previous larger study 32 indicate that Lrig1-expressing cells are able to contribute to formation of Tuft cells, suggesting their role in tissue maintenance. While this manuscript was under consideration, another study by Choi et al .…”
Section: Discussionmentioning
confidence: 72%
“…DCLK1 is overexpressed in many cancers, including colon, pancreas, liver, kidney [ 11 ], and esophageal cancer [ 9 , 12 15 ]. Studies from us and others supported that DCLK1 expression is critical for cancer growth, EMT, metastasis, and cancer cell self-renewal [ 9 , 14 , 16 18 ]. The functional interdependence between EMT-associated transcription factors and enhanced self-renewal highlights the common mechanism involved in their regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It also has been reported that DCLK1-expressing cells are expanded in an ulcer, 12 as well as in response to loss of parietal cells. 37 We observed that DCLK1 was up-regulated significantly in the regenerated epithelium ( Figures 3 A–C and 5 C ). Immunofluorescence showed that DCLK1-positive cells also expressed SOX9, whereas a large number of SOX9-positive cells did not co-express with DCLK1 ( Figure 5 D ).…”
Section: Resultsmentioning
confidence: 71%
“… 12 , 19 , 24 , 38 It has been reported that DCLK1 is up-regulated in response to a loss of parietal cells and metaplasia, including ulcerated tissue, but its functional role remains unknown. 12 , 37 Because DCLK1-positive cells were not positive for Ki67, they likely do not function as stem/progenitor cells. In the ulcer, UEA-1–positive cells expanded deep into the gland along with GSII- or TFF2-positive cells.…”
Section: Discussionmentioning
confidence: 99%